Accounting Environment Readiness for The Application of International Financial Reporting Standards (IFRS) in KSA: An analysis Study (2016 - 2017) - Ahmed, Shihabeldeen Mohamed; Yousif, AbuBaker Ahmed (Journal of Economic, Administrative and Legal Sciences, 2025)
This study aims to identify and recognize readiness of Saudi setting to apply the international standards of financial reports and statements. The study has approached the findings concluded by universities in terms of update and development of curriculums of accounting to cope and match with the international standards of financial reports and statements. The research problem to acknowledgement of Accounting Environment Readiness for The Application of International Financial Reporting Standards, and the importance of research about decision making from king of Saudia Arabia to apply the international standards of financial reports and statements. To this aim, the researcher has proceeded to develop a questionnaire for collecting data and information from members of the sample group. The sample group was composed of two categories as follows: members of teaching staff in accounting departments in Saudi universities; and chartered accountants employed by audit and accounting offices in Jeddah. After distributing and collecting the questionnaires, the number of questionnaires which were valid for statistical analysis purpose was standing at 79.  care shall be given to conducting academic research and studies which are concerned with applying such international standards of financial reports and statements. Seminars and symposiums related to application of the international standards of financial reports and statements shall be held.
Keywords: Accounting Environment; Readiness for The Application; International Financial Reporting Standards (IFRS); KSA